Effects of Gender, Test Anxiety and Test Items Scrambling on Students Performance in Mathematics: A Quasi-Experimental Study - Owan, Valentine Joseph (World Journal of Vocational Education and Training, 2020)
The relative contributions of gender, test anxiety and test items scrambling on performance in Mathematics has been widely assessed, although there is an inconclusive argument regarding the magnitude of such effects. This study was designed to contribute to this debate, while also being the first study to evaluate the interactive effects of the three dimensions of test anxiety (worry, emotion and total) on performance in Mathematics. A systematic random sample of 1,358 SS3 students participated in a quasi-experiment. Data were obtained using the Test Anxiety Scale (TAI) (Spielberger, 1980) and a Mathematics Achievement Test (MAT) developed by Etuk (2019). Findings indicated that there was no significant gender difference on performance; tests anxiety and items scrambling had significant effects on performance in Mathematics respectively; low students’ performance in Mathematics was associated with high test anxiety and test items arrangement from complex to simple; there was a significant interaction of test anxiety worry, emotion and total on performance in Mathematics. It was concluded that gender does not play a significant role in the performance of students in mathematics. Test anxiety in terms of worry, emotion and total affect the performance of students in Mathematics. Based on the conclusions, relevant implications are discussed.